1980
DOI: 10.1126/science.7384806
|View full text |Cite
|
Sign up to set email alerts
|

Tritiated Imipramine Binding Sites Are Decreased in Platelets of Untreated Depressed Patients

Abstract: The high-affinity binding of triatiated imipramine to platelet membranes was compared in samples from 16 untreated depressed women and 21 age-matched controls of the same sex. The maximal binding in the depressed group was significantly lower than that of the controls, although the affinity constants were similar. These results suggest that binding of tritiated imipramine in human platelets may represent a biochemical index of depression, possibly reflecting similar changes in the brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
70
1
3

Year Published

1981
1981
1996
1996

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 433 publications
(79 citation statements)
references
References 14 publications
5
70
1
3
Order By: Relevance
“…The presence of endogenous antidepressant-like sub stances has been suggested ever since the possible pharma cological relationship between changes in presynaptic sites in imipramine binding and manic depressive disor ders was first reported (1). Recently, it has been reported that [3H]imipramine binding sites and [3H]paroxetine binding sites that regulate 5-hydroxytryptamine (5HT) up take are modulated by unidentified endogenous sub stance(s) in human plasma (2)(3)(4)(5) and in rat brain and plas ma (6 9 (13,14).…”
mentioning
confidence: 99%
“…The presence of endogenous antidepressant-like sub stances has been suggested ever since the possible pharma cological relationship between changes in presynaptic sites in imipramine binding and manic depressive disor ders was first reported (1). Recently, it has been reported that [3H]imipramine binding sites and [3H]paroxetine binding sites that regulate 5-hydroxytryptamine (5HT) up take are modulated by unidentified endogenous sub stance(s) in human plasma (2)(3)(4)(5) and in rat brain and plas ma (6 9 (13,14).…”
mentioning
confidence: 99%
“…3H-Imipramine binding sites are reduced following electrolytic lesions of the dorsal raphe and 5,7-dihydroxytrypta mine lesions (22,23), and the decrease in binding parallels the reduction in 5-HT uptake capacity (21). Moreover, several authors have suggested that these sites are clinically impor tant, since a decrease in 3H-imipramine bind ing sites (8,24,25) as well as a decrease in 5 HT uptake (9) was reported in the platelets of depressed patients. These findings suggest that these binding sites are regulated by unidenti fied endogenous ligands.…”
Section: Discussionmentioning
confidence: 99%
“…This recognition sites labeled with 3H -imipramine have been shown to be distinct but allosterically coupled with the serotonin (5-hydroxytryptamine, 5-HT) transport system (5-7). Several lines of evidence suggest that these sites are clinically important since a de crease in 3H-imipramine binding sites (8) as well as a decrease in 5-HT uptake (9) were re ported in platelets of depressed patients.…”
mentioning
confidence: 99%
“…PLATELET PREPARATION Platelets fo r the binding studies were obta ined using a mod ification of the methods of Briley et al ("1979Briley et al (" , 1980 and As. 1rch et .11.…”
Section: Methodsmentioning
confidence: 99%